(untitled) (Bangladesh Journal of Medical Science, 2022)
Glucose-6-phosphate dehydrogenase deficiency (G6PD) is a common X-linked genetic condition among Malaysians that have largely caused acute intravascular haemolysis. In G6PD deficient children, the phenomenon of rhabdomyolysis and myoglobinuria is a rare complication as muscle has more resistant to undergo acute myolysis. A 22-month-old Malay child was presented with severe anaemia following with ingestion of large amount of fava beans. He then developed into acute kidney injury together with the laboratory findings of intravascular haemolysis, rhabdomyolysis, and the presence of multi-systems bloods derangement. He showed positive response to hyperhydration, haemodialysis and blood transfusions. Bangladesh Journal of Medical Science Vol. 21 No. 03 July’22 Page: 741-744